2017
DOI: 10.1016/j.drugalcdep.2017.05.039
|View full text |Cite
|
Sign up to set email alerts
|

N -Acetylcysteine reduces cocaine-cue attentional bias and differentially alters cocaine self-administration based on dosing order

Abstract: Background Disrupted glutamate homeostasis is thought to contribute to cocaine-use disorder, in particular, by enhancing the incentive salience of cocaine stimuli. n-Acetylcysteine might be useful in cocaine-use disorder by normalizing glutamate function. In prior studies, n-acetylcysteine blocked the reinstatement of cocaine seeking in laboratory animals and reduced the salience of cocaine stimuli and delayed relapse in humans. Methods The present study determined the ability of maintenance on n-acetylcyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 52 publications
(68 reference statements)
0
6
1
Order By: Relevance
“…n-Acetylcysteine maintenance generally did not affect physiological outcomes, with breath alcohol concentrations and blood pressure readings being similar across dose conditions. Although we observed increases in heart rate during n -acetylcysteine maintenance, a number of other studies have not observed this effect in populations without alcohol use disorder (e.g., Bolin et al, 2017 ; Leelarungrayub et al, 2011 ; Hirai et al, 2017 ), so future work is needed to confirm how n -acetylcysteine affects heart rate in individuals with alcohol use disorder.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…n-Acetylcysteine maintenance generally did not affect physiological outcomes, with breath alcohol concentrations and blood pressure readings being similar across dose conditions. Although we observed increases in heart rate during n -acetylcysteine maintenance, a number of other studies have not observed this effect in populations without alcohol use disorder (e.g., Bolin et al, 2017 ; Leelarungrayub et al, 2011 ; Hirai et al, 2017 ), so future work is needed to confirm how n -acetylcysteine affects heart rate in individuals with alcohol use disorder.…”
Section: Discussioncontrasting
confidence: 53%
“…The n -acetylcysteine maintenance period was selected based on our previous work with n -acetylcysteine ( Bolin et al, 2017 ), showing that a similar n -acetylcysteine regimen reduced cocaine self-administration in a maintenance-order dependent manner and reduced cocaine attentional bias. We also selected the maintenance period based on research published by other laboratories ( Amen et al, 2011 ).…”
Section: Methodsmentioning
confidence: 99%
“…This has been found for several cognitive functions (Skvarc et al, 2017), but whether NAC also has an effect on cognitive control in SUDs remains to be investigated. Although studies exist on the effect of NAC on induced craving (in which WM is used as a distractor; Amen et al, 2011) and the positive effect of NAC on attentional bias (Bolin et al, 2017), in our study we specifically examined the effect of NAC to improve cognitive control in SUDs.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials demonstrate that NAC attenuated cocaine use and decreased desire to use cocaine (LaRowe et al 2007;Mardikian et al 2007). Recent clinical trials also support the ability of NAC to reduce incentive salience for cocaine cues (Levi et al 2017) and delay relapse in cocaine-abstinent subjects (LaRowe et al 2013), suggesting that NAC may be therapeutically beneficial in maintaining abstinence and/or preventing relapse. Another interesting strategy is the development of cocaine vaccines.…”
Section: Psychostimulantsmentioning
confidence: 93%